Two angles for an analysis of Brazil’s regional projection: the view of United States State Departament and the “brasiguaios” issue - Barbosa dos Santos, Fabio Luis; Universidad Federal de São Paulo (Pontificia Universidad Javeriana, 2015)
This article discusses the meaning of Brazil’s current regional projection, assessing in one hand the vision that the United States has about this issue and on the other hand the political implications of the recent political crisis in Paraguay. The text unfolds through three steps. At first we focus the context in which projects of regional integration in the Americas reemerge in the 1990s. Then we analyse statemants of the United States State Departament related to this matter. At last, we discuss the relations between the Brazilian State and Paraguay, focusing on the “brasiguaios” issue as a case study that illustrates the paradoxes faced by the Brazilian diplomacy in the region. My hypothesis is that as we approach both the way that Brazil’s regional projection is seen by the hegemonic power in the continent and the consequences of this movement in a country where Brazilian influence is historically sensitive, offers important evidence to evaluate the meaning of the ongoing regional integration process led by Brazil in the subcontinent, questioning the notion that this process contradicts United States’ interests and points to a new pattern of development.